IDDF2018-ABS-0207 Winning the war against colon cancer: chemo-preventive potential of novel streptomyces species derived from mangrove forest in malaysia. (June 2018) - Lee, Learn-Han; Ser, Hooi-Leng; Mutalib, Nurul-Syakima Ab; Khan, Tahir Mehmood; Chan, Kok-Gan; Goh, Bey-Hing
Abstract : Background: Chemoresistance remains a major challenge in cancer therapy including colon cancer (CC). Researchers have been searching for efficient, potent drug candidates to combat against CC. Microorganisms are 'mini-factories' for bioactive compounds that can be exploited as therapeutic agents. The members of the genus Streptomyces is well-known as prolific drug producers, given that over 10 000 bioactive metabolites have been recovered from these filamentous bacteria. Streptomyces species living in the dynamic mangrove forest are placed under constant pressure to thrive in such harsh environment, which is suggested to promote the production of interesting bioactive metabolites with anticancer properties. This project aims to investigate the cytotoxic and antioxidant activities of an extract derived from novel Streptomyces species isolated from mangrove forest in Malaysia. Methods: Four novel Streptomyces species (designated as MUSC 26 T, MUSC 136 T, MUSC 149 T and MUSC 164 T ) were identified from the poorly explored mangrove sediment (East Coast, Peninsular Malaysia) using polyphasic approach. As an attempt to explore the bioactive potential of these mangrove-derived streptomycetes, extracts of these strains were prepared via fermentation and chemical extractions before performing in vitro biochemical and screening assays using cancer cell lines. Results: All of the methanolic extracts of these strains were shown to possess significant antioxidant activities. Among these strains, strain MUSC 136 T displayed highest cytotoxic activity against colon cancer cell line HCT-116, killing more than half of them at 400 ug/mL. In order to understand the mechanisms of actions involved, the levels of intracellular glutathione (GSH) was evaluated as this ubiquitous non-protein thiol is crucial for cell survival. A drastic increase in the proportion of cells undergoing GSH depletion was observed higher (44.11%± 6.21%) as compared to control. Along with this observation, higher expression level of tumour suppressor protein, p53 was observed in cells treated with MUSC 136 T extract. Thus, we postulate that treatment of MUSC 136 T extract might potentially trigger the activation of p53-dependent apoptosis pathways (figure 1). Conclusions: Altogether, these findings highlight the importance of novel strain discovery from the underexplored areas, like mangrove forest, particularly in search of chemopreventive agents.